PW 1474 Health action for children and youth at risk. (November 2018) - Menezes, Barbara; Oliveira, Dina; Chaves, Nicole; Silva, Andreia; Figueira, Fátima; Prazere, Vasco; Chaves, Marta; Machado, Daniela; Costa, Luísa Horta e; Mentes, Odete; Constantina, Maria; Marreiros, Maria; et al.
Abstract : Created by the order no. 31292/2008, the Health Action for Children and Youth at Risk, has as its main goal the creation of a structured response, in the National Health Service, to the phenomenon of maltreatment through the development of the 'National Network of Support Centers for Children and Youth at Risk' both at primary health care and hospitals with pediatric care. The objective of this study is to demonstrate Portugal's evolution regarding the implementation of the 'National Network of Support Centers for Children and Youth at Risk'. The data analysis was based on the national official reports from the Directorate-General of Health. According to the first report (2010) report there were about 189 centers in primary health care and Hospitals and record of 2815 cases signaled through the network. Of the identified cases about 72% were regarding negligence, 9% physical abuse, 7% sexual abuse and 12% psychological abuse/maltreatment. In 2016 there were identified about 268 centers and there were record of 8927 cases signaled. Of the cases signaled about 67% were regarding negligence, 7% physical abuse, 6% sexual abuse and 20% psychological abuse. In order to reinforce prevention and early detention skills of health professionals, a computerized register of the family risk assessment has been incorporated into the National Program for Child and Youth Health (normative circular 010/2013 of the General Directorate of Health). This register is available, as a parameter to be assessed, at national level in all child and juvenile health surveillance (0–18 years) consultations. This register allows not only the registration of risk factors and protection of each child/family, but also of situations of abuse and its signaling to the network teams of the National Health Service.